The Blood–Brain Barrier—A Key Player in Multiple Sclerosis Disease Mechanisms - Thomas Gabriel Schreiner; Constantin Romanescu; Bogdan Ovidiu Popescu (Biomolecules, 2022)
Over the past decade, multiple sclerosis (MS), a chronic neuroinflammatory disease with severe personal and social consequences, has undergone a steady increase in incidence and prevalence rates worldwide. Despite ongoing research and the development of several novel therapies, MS pathology remains incompletely understood, and the prospect for a curative treatment continues to be unpromising in the near future. A sustained research effort, however, should contribute to a deeper understanding of underlying disease mechanisms, which will undoubtedly yield improved results in drug development. In recent years, the blood–brain barrier (BBB) has increasingly become the focus of many studies as it appears to be involved in both MS disease onset and progression. More specifically, neurovascular unit damage is believed to be involved in the critical process of CNS immune cell penetration, which subsequently favors the development of a CNS-specific immune response, leading to the classical pathological and clinical hallmarks of MS. The aim of the current narrative review is to merge the relevant evidence on the role of the BBB in MS pathology in a comprehensive and succinct manner. Firstly, the physiological structure and functions of the BBB as a component of the more complex neurovascular unit are presented. Subsequently, the authors review the specific alteration of the BBB encountered in different stages of MS, focusing on both the modifications of BBB cells in neuroinflammation and the CNS penetration of immune cells. Finally, the currently accepted theories on neurodegeneration in MS are summarized.